Pendampingan Pembuatan Bahan Ajar Digital untuk Guru sebagai Upaya Penguatan Implementasi Kurikulum Merdeka di SMP Negeri 5 Takengon - Widya, Widya; Afriyani, Mice Putri; Fadieny, Nurul; Trianasari, Dila; Raseukina, Geubri (Universitas Pahlawan Tuanku Tambusai, 2023)
Digital teaching materials can support the implementation of the Merdeka curriculum. Digital teaching materials can increase student motivation and interest in learning because it looks attractive and interactive, and students can understand the material comprehensively. At SMP Negeri 5 Takengon, there is no availability of digital teaching materials. Based on these problems, the implementation team and the school principal carried out mentoring activities for the creation of digital teaching materials for teachers at Takengon 5 Public Middle School. Assistance was carried out through 10 meetings that introduced teachers to several applications for creating digital teaching materials. Based on some assistance, information was obtained that there was an increase in the ability of teachers to develop digital teaching materials, several digital teaching materials were completed, and teachers were motivated to learn more about digital teaching materials.